2012
DOI: 10.5194/bg-9-4607-2012
|View full text |Cite
|
Sign up to set email alerts
|

Bioerosion by microbial euendoliths in benthic foraminifera from heavy metal-polluted coastal environments of Portovesme (south-western Sardinia, Italy)

Abstract: Abstract.A monitoring survey of the coastal area facing the industrial area of Portoscuso-Portovesme (south-western Sardinia, Italy) revealed intense bioerosional processes. Benthic foraminifera collected at the same depth (about 2 m) but at different distances from the pollution source show extensive microbial infestation, anomalous Mg/Ca molar ratios and high levels of heavy metals in the shell associated with a decrease in foraminifera richness, population density and biodiversity with the presence of morph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 70 publications
(61 reference statements)
4
17
0
Order By: Relevance
“…These studies revealed high concentrations of Hg, Cd, Pb, and Zn that correspond to low species diversity, low population density and more frequent abnormal specimens. The foraminiferal assemblages recognised by Cherchi et al (2009Cherchi et al ( , 2012 appear very similar to those retrieved in the PS4 sample.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…These studies revealed high concentrations of Hg, Cd, Pb, and Zn that correspond to low species diversity, low population density and more frequent abnormal specimens. The foraminiferal assemblages recognised by Cherchi et al (2009Cherchi et al ( , 2012 appear very similar to those retrieved in the PS4 sample.…”
Section: Discussionsupporting
confidence: 52%
“…Cluster A includes stations characterised by a lower content of contaminants (PAH and trace metals), whereas Cluster B (most polluted) comprises samples located mainly in the harbour areas of La Maddalena (LM6, LM7), S. Stefano (LM8, LM9), Calasetta (PS4) and Porto Torres (PT2, PT3, PT4), which are characterised by high levels of contaminants, muddy sediments and low values of biotic indices. The stressed environmental conditions in the southwestern area of Sardinia (Portoscuso-Portovesme) have also been highlighted in previous studies (Cherchi et al, , 2012 through analysis of the biotic indices of foraminifera tests and chemical analysis of the sediments (Schintu et al, 2009). These studies revealed high concentrations of Hg, Cd, Pb, and Zn that correspond to low species diversity, low population density and more frequent abnormal specimens.…”
Section: Discussionmentioning
confidence: 80%
“…The finding is in accordance with a recent study, that revealed FN numbers ranging from 0.6 to 45.8 g -1 in the most polluted area harbor areas [9]. Low foraminiferal abundances were also recorded from other sites impacted by oil discharges (PAH's) and heavy metals [68,[71][72][73][74] and commonly goes hand in hand with a decrease in species richness [48,50]. In severely polluted but regularly flushed harbor areas, where rates of seawater exchange are high and water residence time remains short, high diversity assemblages, composed of both marine, brackish and marginal marine biotas, continue to be promoted [75].…”
Section: Influence Of Pollutionsupporting
confidence: 91%
“…ecosystems, e.g., through abiotic dissolution (e.g., (Green et al, 1993)) and bioerosion (e.g., (Cherchi et al, 2012)), transformation of the shells into lime mud, i.e., the important matrix of both recent and ancient calcareous sediments (e.g., (Debenay et al, 1999)), etc. Here, while the abiotic dissolution and mechanical damage contributed only little, the majority (>70%) of the substrate shells showed at least some signs of bioerosion, with 13% being highly bioeroded.…”
Section: Discussionmentioning
confidence: 99%